PENGARUH KELENGKUNGAN LENSA POLYCARBONATE TERHADAP PEMBUATAN BEVEL UNTUK FRAME SEMI RIMLESS DENGAN MESIN AUTO GROOVER - Opep Nugraha; Bunyamin Rizki Abdillah; Hanie Supandi (Akademi Refraksi Optisi dan Optometry Gapopin, 2023)
Auto groover is a tool used to produce lenses with hidden bevels so that there are parts of the rope tied to the resulting bevel and are used on semi rimless or half frame types. This can be affected by the thickness and curvature of the lens, so this study wants to prove how exactly are polycarbonate lenses made with good bevels. This research uses a descriptive method. The initial screening was conducted by reading the titles and abstracts by using search engine with keyword “Polycarbonate Lens AND Bevel Type AND Autogroover” in the journals ScieneDirect, Plos One, and in Bahasa Google Scholar. Based on the results of the journal search it was concluded that making bevels in an optical dispensing laboratory using an autogroover machine requires high precision and skill from practitioners so that glasses can be produced according to the type of frame chosen by the patient.